PENERAPAN PERHITUNGAN PPH 21 BERDASARKAN UU NOMOR 7 TAHUN 2021 PADA PEGAWAI TETAP PT X - Rachman, Gilang Fachrizal; Widodo, Ulfa Puspa Wanti (TEMA, 2023)
In 2021, Indonesia is affected by Covid-19. With this outbreak, the economic sector experienced a significant impact. The government's role in dealing with this outbreak’s impact ischanging Law (UU) No. 36 of 2008 to Law No. 7 of 2021. This change in law has caused the tariff layer on PPh 21 to change, which was originally a 5% rate imposed on taxpayers' taxes with an income of IDR 50 million and becomes 5% for taxpayers with an income of IDR 60 million. In addition, this law has an additional tariff, whereby taxpayers with income above Rp. 500 million are subject to a rate of 30%, so income above Rp. 5 billion is subject to a rate of 35%. This study aims to find out the application of PPH 21 calculations based on Law Number 7 of 2021 on PT X employees. The method used in this study uses a descriptive qualitative method. The results of the study stated that the PPh 21 calcula-tion carried out by PT X was following the provisions stipulated in Law Number 7 of 2021.